2016
DOI: 10.1038/srep37959
|View full text |Cite
|
Sign up to set email alerts
|

TDB protects vascular endothelial cells against oxygen-glucose deprivation/reperfusion-induced injury by targeting miR-34a to increase Bcl-2 expression

Abstract: Prolonged ischemia can result in apoptotic death of vascular endothelial cells and lead to ischemic vascular diseases including vascular dementia, arteriosclerosis and brain oedema. Finding protective strategies to prevent this is therefore an urgent mission. Recent studies have shown that dysregulation of microRNAs (miRNAs) can lead to imbalance of Bcl-2 family proteins and mitochondrial dysfunction, leading to further damage of vascular cells under ischemic conditions. However, whether miRNAs can be used as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
30
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 46 publications
(60 reference statements)
4
30
0
Order By: Relevance
“…caspase-9 cleaves and activates procaspase-3, a downstream executioner caspase protein, which cleaves various 'death substrates' and thereby triggers the apoptotic cell phenotype. A previous study demonstrated that the knockdown of miR-34a altered the integrity of the mitochondrial outer membrane and increased the release of cyto c from mitochondria, finally activating the caspase-mediated apoptotic pathway in vascular Ecs (20). In the present study, the results showed that the knockdown of miR-34a inhibited cleaved-caspase-3, -8, -9, Bax and cleaved-PARP, and increased Bcl-2 in the ox-LdL-treated HUVEcs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…caspase-9 cleaves and activates procaspase-3, a downstream executioner caspase protein, which cleaves various 'death substrates' and thereby triggers the apoptotic cell phenotype. A previous study demonstrated that the knockdown of miR-34a altered the integrity of the mitochondrial outer membrane and increased the release of cyto c from mitochondria, finally activating the caspase-mediated apoptotic pathway in vascular Ecs (20). In the present study, the results showed that the knockdown of miR-34a inhibited cleaved-caspase-3, -8, -9, Bax and cleaved-PARP, and increased Bcl-2 in the ox-LdL-treated HUVEcs.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al (25) demonstrated that the inhibition of miR-155 improved high glucose-induced Ec injury by suppressing the activation of nuclear factor-κB. miR-34a is upregulated in atherosclerotic samples and is involved in the progression of atherosclerosis (21), in addition to possessing pro-apoptotic effects on Ecs (20). Previous miRNA microarray analysis confirmed that the levels of miR-34a are increased in the serum of patients with atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bcl-2 related X (Bax) is a homologous to Bcl-2 and an apoptosispromoting gene in the Bcl-2 gene family. [40][41][42] Overexpression of Bax can antagonize the protective effect of Bcl-2 and lead to cell death. Our results shown that Bcl-2 were down expression in miR-34a/CLMBs group and miR-34a/CLMBs and sPD-1/CLMBs mixed group.…”
Section: Discussionmentioning
confidence: 99%